Digital Typography: Evolution and Communication in the Technological Age - Srifar, Kittituch (Siam Communication Review, 2025)
This academic article explores the evolution of digital typography from its origins in the era of electronic calculators to its current status as an integral part of the digital revolution. By analyzing the role of digital typography as a representation of technological and social change, the study covers aspects of design, application in various media, and influence on contemporary communication culture. The results indicate that digital typography not only reflects the limitations and advances in technology but also serves as evidence of the Cold War era competition and the transition to the digital age.